Agreements Relating to the Settlement of Industrial Disputes – de Lege Lata and de Lege Ferenda Comments - Hajn, Zbigniew (Acta Universitatis Lodziensis. Folia Iuridica, 2025)
The article presents the views of the doctrine and judicial case law on the legal nature of social partner agreements related to an industrial dispute. It also presents the dispute over the legal character of these agreements against a broader background of views on the legal basis for recognising the normative character of agreements other than a collective agreement that define the content of the employment relationship. Finally, the Author of the article comes to the conclusion that finding a satisfactory solution to the problems related to this dispute is not possible on the basis of the current legal provisions. As a result, the Author proposes and justifies an amendment to the relevant provisions consisting in the explicit recognition by the law that all written agreements defining working conditions and concluded by the authorised social partners are, regardless of their name, collective agreements.